The The Effectiveness of Problem Oriented Project Based Learning (POPBL) Towards Scientific Literacy in Public Senior High School 1 Cluring Banyuwangi - Suwistika, Rima; Ibrohim, Ibrohim; Susanto, Hendra; Maisaroh, Siti (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
There are various project-based learning models that can encourage scientific literacy. This study aims to analyze the effectiveness of the POPBL model in increasing high school students scientific literacy. This quasi-experimental research used a nonequivalent control group design. The population of this study was students of eleventh graders of Science at Public Senior High School 1 Cluring, with two eleventh classes of Science 1 and Science 2 as samples. The data collection method is using scientific literacy test. The data analysis used an analysis of the covariance test. The results showed that POPBL was effective in increasing the scientific literacy of SMAN 1 Cluring students.